Old-time conversations finding health, happiness and community through traditional music - Evans, Craig A. 1952- (McFarland & Company, Inc., Publishers, 2024)
"Approaching 50, disillusioned with business, the author found himself irresistibly drawn back to the joy and sense of community he had witnessed music bring in his youth. Inspired by this rediscovered passion, he embarked on a remarkable 12-year odyssey, capturing the stories of artisans, performers, and teachers of traditional music across North America, all preserved in this volume. These unique individuals represent the heart and soul of old-time music. Those interviewed include instrument builders Bart Reiter, Doc Huff, Pete Ross, Zachary Hoyt, Bill Rickard, and William Seeders Mosheim; old-time performers Rayna Gellert, David Holt, Sparky Rucker, Claire Milliner, Mac Benford, Sheila Kaye Adams, Paul Brown and John McCutcheon; and historians and authors Dwight Diller, Dr. Bill Malone, Don Flemons, and Tim Brooks."--
Keywords: Geschichte 1970-2020; Musikinstrumentenbauer; Volksmusiker; Folk music; USA; Old-time music / History and criticism; String band music / United States / History and criticism; Folk musicians / United States / Interviews; Banjoists / United States / Interviews; Banjo makers / United States / Interviews; Musicologists / United States / Interviews; Evans, Craig R. / 1952-; String band, Musique de / États-Unis / Histoire et critique; Musiciens traditionnels / États-Unis / Entretiens; Banjoïstes / États-Unis / Entretiens; Musicologues / États-Unis / Entretiens; MUSIC / Genres & Styles / Folk & Traditional; interviews; Interviews; Interview